KEARIFAN LOKAL DIPLOMASI DENGAN ROH HALUS DALAM CERPEN “PERTEMUAN DENGAN ROH HALUS” KARYA W.S RENDRA - I Ketut Sudewa (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
In the short story “Peremuan Dengan Roh Halus”, W.S Rendra revealed about the local wisdom of the Wonogiri community in Central Java and W.S Rendra's views on this local wisdom. This was conveyed by a unique story technique, namely the storytelling technique. This local wisdom can be a medium of learning in recognizing various local wisdoms that exist in Indonesian society. By knowing and understanding various local wisdoms that exist in Indonesia, it is hoped that they can become a glue and unifier of the nation, especially in maintaining the nation's culture which is known to be very good. This study discusses the local wisdom contained in the short story "Pertemuan Dengan Roh Halus" and the author's attitude towards the local wisdom. The theory used is semiotic theory. The method used is a literature study method with reading, listening, note-taking, and interpretative techniques.The results show that the local wisdom contained in the short story "Pertemuan Dengan Roh Halus" is that the Wonogiri community believes in the existence of spirits and their world, believes in the existence of ngelambrang, and there is a dialogue between humans and spirits whose author's term is diplomacy with spirits. The short story also depicts W.S Rendra's view of local wisdom, namely that there is a clear difference between the lives of humans and spirits.